Valor diagnóstico de la histerosalpingografía por fluoroscopia en comparación con la laparoscopia en el estudio de mujeres con infertilidad - Cortez Cardoso, Paolo Junior (2020)
Procedures such as hysterosapingography have been re-emerging in the last 10 years due to the demand for infertility cases in national and international territory and in the city of Trujillo it is no exception, accompanied by a laparoscopic approach, they are of mutual help for treatment and subsequent fertilization of women of childbearing age. Objective: To demonstrate if the results of hysterosalpingography in comparison to diagnostic laparoscopy are consistent in the identification of tubal pathology. Methods: A bibliographic search of various studies was carried out, review of procedures performed at the Víctor Lazarte Echegaray Hospital of women in childbearing age with a diagnosis of infertility.